Process development and preclinical evaluation of a major Plasmodium falciparum blood stage vaccine candidate, Cysteine-Rich Protective Antigen (CyRPA) - Somanathan, Anjali; Mian, Syed Yusuf; Chaddha, Kritika; Uchoi, Seemalata; Bharti, Praveen K.; Tandon, Ravi; Gaur, Deepak; Chauhan, Virander Singh (Frontiers in Immunology, 2022)
Plasmodium falciparum Cysteine-Rich Protective Antigen (CyRPA) is an essential, highly conserved merozoite antigen that forms an important multi-protein complex (RH5/Ripr/CyRPA) necessary for erythrocyte invasion. CyRPA is a promising blood-stage vaccine target that has been shown to elicit potent strain-transcending parasite neutralizing antibodies. Recently, we demonstrated that naturally acquired immune anti-CyRPA antibodies are invasion-inhibitory and therefore a correlate of protection against malaria. Here, we describe a process for the large-scale production of tag-free CyRPA vaccine in E. coli and demonstrate its parasite neutralizing efficacy with commonly used adjuvants. CyRPA was purified from inclusion bodies using a one-step purification method with high purity (>90%). Biochemical and biophysical characterization showed that the purified tag-free CyRPA interacted with RH5, readily detected by a conformation-specific CyRPA monoclonal antibody and recognized by sera from malaria infected individuals thus indicating that the recombinant antigen was correctly folded and retained its native conformation. Tag-free CyRPA formulated with Freund’s adjuvant elicited highly potent parasite neutralizing antibodies achieving inhibition of >90% across diverse parasite strains. Importantly, we identified tag-free CyRPA/Alhydrogel formulation as most effective in inducing a highly immunogenic antibody response that exhibited efficacious, cross-strain in vitro parasite neutralization achieving ~80% at 10 mg/ml. Further, CyRPA/Alhydrogel vaccine induced anti-parasite cytokine response in mice. In summary, our study provides a simple, scalable, cost-effective process for the production of tag-free CyRPA that in combination with human-compatible adjuvant induces efficacious humoral and cell-mediated immune response.